2022
DOI: 10.6023/cjoc202107018
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Synthesis of Pyrazine and Ketone Derivatives by Unsymmetrical Triazolyl-Naphthyridinyl-Pyridine Copper

Abstract: ( a 江南大学化学与材料工程学院 教育部合成与生物胶体重点实验室 江苏无锡 214122)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…13 Recently, we synthesized several nitrogen-containing heterocycle-based catalysts which displayed some catalytic reactivity in the borrowing hydrogen and dehydrogenation reactions. 14,15 However, a limitation of these catalysts was that reactions with the C3-alkylated indoles and triazine derivatives were unsuccessful, which indicated that it is necessary and urgent to develop efficient and highly active catalysts. Herein, we synthesized a pyridine and pyrazole-based porous organic polymer (Py-POP) and its corresponding metal polymer Ru@Py-POP, which could be used to catalyze the reactions of indoles with alcohols and biguanides with alcohols (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…13 Recently, we synthesized several nitrogen-containing heterocycle-based catalysts which displayed some catalytic reactivity in the borrowing hydrogen and dehydrogenation reactions. 14,15 However, a limitation of these catalysts was that reactions with the C3-alkylated indoles and triazine derivatives were unsuccessful, which indicated that it is necessary and urgent to develop efficient and highly active catalysts. Herein, we synthesized a pyridine and pyrazole-based porous organic polymer (Py-POP) and its corresponding metal polymer Ru@Py-POP, which could be used to catalyze the reactions of indoles with alcohols and biguanides with alcohols (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Pyridine is a fundamental heterocyclic motif with prevalent presence in molecules associated with human life such as pharmaceuticals, materials, as well as synthetic building blocks . In addition, the pyridines have also been found to possess various other functions such as acting as an organic base, a ligand, as well as single-electron donors . Being inspired by the important applications of pyridine scaffolds, the synthesis of pyridine keeps attracting extensive interest from chemical and related other communities.…”
mentioning
confidence: 99%